Pattern of Non-Strabismic Binocular Vision Dysfunctions among Undergraduate Engineering Students of Vivekananda Global University - Agrahari, Manish; Devi, Varsha; Kumari, Rozy; Verma, Mahendra kumar (Journal of Neonatal Surgery, 2025)
Background: - Our eyes work together binocularly when they are functioning normally. This allows our eyes to view a single image instead of two separate ones. Patients without strabismus who have non-strabismic binocular vision dysfunction (NSBVD) have a visual disorder in which one eye's line of sight is somewhat off-alignment with the other eye's line of sight. The eye muscles are under a lot of strain since they are always attempting to adjust the alignment in order to attain single focus vision [2]. Many people suffer from binocular vision abnormalities that go undetected. Ocular and binocular dysfunction that is not recognized can cause discomfort, which can hinder clinical training and academic achievement. Method: -The cross sectional based study was conducted at Vivekananda Global University, Jaipur, among 190 undergraduates engineering student. CISS score was measured in all the cases. VA for distance, Stereopsis, cover test at far and near were performed. Near point of convergence (NPC), amplitude of accommodation, positive and negative fusional vergence in near and distance, monocular and binocular accommodation facility, positive and negative relative accommodation, monocular estimation method (MEM) and AC/A ratio were evaluated in all participants. Results: -The mean age of the participants was 21.44 ±1.523 ranging from 18 to 26 years of which 75.78% (144) were male and 24.22% (46) were females. And according to the symptom score 62.10% (118) were found being symptomatic and 37.90% (42) were found to being asymptomatic. The percentage of NSBVD was 71.06% among undergraduate engineering students of VGU. Out of 135 participants, 48 of them had accommodative anomaly and 87 of them had vergence anomaly. The prevalence of vergence anomaly was greater than accommodative anomaly. The highest percentage of NSBVD was observed for CI (22.10%) followed by AE (17.89%), FVD (14.73%), AI (6.31%), CE (4.21%), DE (3.15%), Basic exophoria (1.57%) and Accommodative Infacility (1.05%). Conclusion: - This study shows that among the engineering students in the chosen sample, accommodative and vergence disorders are highly prevalent. These early findings suggest that better knowledge, diagnosis, and treatment of binocular dysfunctions are required. If an accommodative or vergence issue is discovered, prompt and efficient therapy should be recommended. Student will be able to reach their maximum potential if NSBVD is identified and treated promptly